Cultivating networks and mapping social landscapes: How to understand restoration governance in Rwanda. (May 2021) - Buckingham, Kathleen; Arakwiye, Bernadette; Ray, Sabin; Maneerattana, Ornanong; Anderson, Will
Highlights: Social network analysis was used to map flows of information and collaboration, tree seedlings, and finance to understand who influences restoration in Rwanda. Priorities and values assessment helped identify where there is alignment and difference across community, district and national scales. Farmers remain the key implementers of restoration, but they do not receive the resources they need. Diverse, reliable, and resilient networks of information, finance, and seedlings will be essential for the restoration movement to be sustainable. There is a disconnect between the goals for restoration at the different scales. It is important to consider how the district level can act as a mediator for different priorities between the community and national level. Abstract: This study focuses on environmental governance in Rwanda through a social network lens, with the aim to understand actors' connections, their priorities and their values within the restoration landscape at the national, district and community scales in Gatsibo. Diverse, reliable, and resilient networks of information, finance, and seedlings are essential for the restoration movement to be sustainable. The study identifies that key resource flows are not directly accessible to the farmers, who are the key implementers of restoration in Rwanda. The study identifies the need to first understand and then strengthen these networks by mapping actors' resource flows, priorities and values, and then developing a strategy for change. By considering actor networks, restoration interventions can be more efficient regarding resources, collaboration and outreach. Moreover, conflicts and bottlenecks can be more easily anticipated.